Therapeutic Doses of Nonsteroidal Anti-Inflammatory Drugs Inhibit Osteosarcoma MG-63 Osteoblast-Like Cells Maturation, Viability, and Biomineralization Potential - E. De Luna-Bertos; J. Ramos-Torrecillas; O. García-Martínez; A. Guildford; M. Santin; C. Ruiz (The Scientific World Journal)
Nonsteroidal anti-inflammatory drugs (NSAIDs) are frequently used to reduce pain and inflammation. However, their effect on bone metabolisms is not well known, and results in the literature are contradictory. The present study focusses on the effect of dexketoprofen, ketorolac, metamizole, and acetylsalicylic acid, at therapeutic doses, on different biochemical and phenotypic pathways in human osteoblast-like cells. Osteoblasts (MG-63 cell line) were incubated in culture medium with 1–10 μM of dexketoprofen, ketorolac, metamizole, and acetylsalicylic acid. Flow cytometry was used to study antigenic profile and phagocytic activity. The osteoblastic differentiation was evaluated by mineralization and synthesis of collagen fibers by microscopy and alkaline phosphatase activity (ALP) by spectrophotometric assay. Short-term treatment with therapeutic doses of NSAIDs modulated differentiation, antigenic profile, and phagocyte activity of osteoblast-like cells. The treatment reduced ALP synthesis and matrix mineralization. However, nonsignificant differences were observed on collagen syntheses after treatments. The percentage of CD54 expression was increased with all treatments. CD80, CD86, and HLA-DR showed a decreased expression, which depended on NSAID and the dose applied. The treatments also decreased phagocyte activity in this cellular population. The results of this paper provide evidences that NSAIDs inhibit the osteoblast differentiation process thus reducing their ability to produce new bone mineralized extracellular matrix.